Survey of Availability of Electronic Media for Teaching in Colleges of Education in Oyo State - Daramola, Florence Olutunu (ASEAN Journal of Educational Research and Technology, 2022)
New and emerging technologies challenge the traditional process of teaching and learning and the way education is managed. This study examined the survey and availability of electronic media for teaching in colleges of education in Oyo State, Nigeria. The research design adopt for this study was the descriptive survey research design. The target population for his study includes selected lecturers in Colleges of Education, Oyo State. Simple random sampling techniques were adopted to draw out the sample for the study. A hundred lecturers out of the total population of 196 academic staff of Oyo State Colleges of Education participated. The selection constituted lecturers from all disciplines across the selected institution. The result obtained from this study indicated that some Information and Communication Technology (ICT) facilities were available and adequate: some were available but not adequate while others were not available at all. This implies that inadequate resources could affect the lecturer’s lesson delivery. It was however recommended that ICT facilities should be made available in all institutions of learning to improved teaching-learning processes.